ФИЛОСОФСКИЕ АСПЕКТЫ СМЕНЫ ЛИНГВИСТИЧЕСКОЙ ПАРАДИГМЫ В ОПИСАНИИ ЦЕРКОВНОСЛАВЯНСКОГО ЯЗЫКА (Philological Studies, 2019)
The difficulties of the objective description of Church Slavonic language, which are connected to lacks of the theory as common Slavic linguistic discipline, uncertainty of criteria of the description and object of research are analyzed in the clause.
Keywords: Church Slavonic, book written tradition